Products for Sportspeople Containing Constituents Derived from the Common Bean Phaseolus vulgaris L. (Fabaceae)-A Narrative Literature Review - Kinga Kostrakiewicz-Gierałt (MDPI AG, 2023)
The third-largest land plant family, Fabaceae (Papilionaceae), includes trees, shrubs, and perennial or annual herbaceous plants containing both numerous beneficial constituents (e.g., proteins, carbohydrates, dietary fibre) and antinutrients (e.g., saponins, tannins, phytic acid, gossypol, lectins). The consumption of leguminous plants allows sports people to complete their requirements for nourishment but, on the other hand, it contributes to digestive system ailments. Therefore, the aim of the presented study was to review the experimental articles and patents referring to the application of common (kidney) bean (Phaseolus vulgaris L.)-based nutritional products for athletes. The survey of the literature was carried out according to PRISMA statements by browsing Scopus, PubMed and ISI Web of Science databases, as well as Google Scholar, Google Patents and Espacenet Patent Search engines using factorial combinations of the following keywords: ('common bean' or 'kidney bean' or 'Phaseolus vulgaris') and ('athlete' or 'sport') and ('food' or 'nutrition' or 'diet'). Altogether, 84 patents issued in the years 1995-2023 were noted. The majority of patents were developed by research teams consisting of at least four authors representing scientists affiliated in the United States of America and China. The patents refer to the production of food ingredients, nutritional products, and compositions: (i) for relieving fatigue, enhancing endurance, and increasing muscle mass and strength, (ii) for maintaining physical and mental health, and (iii) for controlling body weight. Moreover, the analysis of 19 original articles indicated the substantial acceptability of meals containing the common bean. To summarize, the performed investigations demonstrate the considerable use of Phaseolus vulgaris in sport nutrition and the growing acceptance of this trend.